2018
DOI: 10.1002/cncr.31907
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled trial of probiotics to reduce the severity of oral mucositis induced by chemoradiotherapy for patients with nasopharyngeal carcinoma

Abstract: BACKGROUND:The objective of this study was to evaluate the effect of a probiotic combination on the severity of oral mucositis (OM), which is a common, unpreventable complication induced by radiochemotherapy in patients with nasopharyngeal carcinoma who undergo concurrent radiochemotherapy (CCRT). METHODS: Eligible patients (n = 99) with locally advanced nasopharyngeal carcinoma who were undergoing CCRT were randomly assigned (2:1) to receive a probiotic combination or placebo during radiochemotherapy, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 32 publications
2
125
0
Order By: Relevance
“…18 Chi et al indicated that intestinal microbiota regulated the growth of liver tumors by regulating the amount of natural killer T (NKT) cell in the mice liver through mediating bile acid metabolites, and the use of combined antibiotics reduced the tumor volumes and weight in mice. 19 Moreover our studies indicated that the probiotic combination (Bifico) contained Bifidobacterium longum, Lactobacillus lactis, and Enterococcus faecium could significantly reduce oral mucositis caused by radiotherapy and chemotherapy in patients with nasopharyngeal carcinoma 20 ; and another combination probiotics of L. infantis, L. acidophilus, E. faecalis, and Bacillus cereus significantly reduced the severity of physiological and microbial disorders induced by partial gastrectomy in patients with gastric cancer. 21 In view of the important role of DSF and gut microbiota in cancer development and treatment, we wonder if intestinal microbes also play a role in affecting the efficacy of DSF in the treatment of cancers.…”
Section: Introductionmentioning
confidence: 77%
“…18 Chi et al indicated that intestinal microbiota regulated the growth of liver tumors by regulating the amount of natural killer T (NKT) cell in the mice liver through mediating bile acid metabolites, and the use of combined antibiotics reduced the tumor volumes and weight in mice. 19 Moreover our studies indicated that the probiotic combination (Bifico) contained Bifidobacterium longum, Lactobacillus lactis, and Enterococcus faecium could significantly reduce oral mucositis caused by radiotherapy and chemotherapy in patients with nasopharyngeal carcinoma 20 ; and another combination probiotics of L. infantis, L. acidophilus, E. faecalis, and Bacillus cereus significantly reduced the severity of physiological and microbial disorders induced by partial gastrectomy in patients with gastric cancer. 21 In view of the important role of DSF and gut microbiota in cancer development and treatment, we wonder if intestinal microbes also play a role in affecting the efficacy of DSF in the treatment of cancers.…”
Section: Introductionmentioning
confidence: 77%
“…There is a growing interest in the applicability of probiotics in OM; largely driven by the effectiveness of probiotics in reducing the severity of intestinal mucositis 18,19 . In this study we showed for the first time that L. reuteri DSM 17938 and PTA 5289 significantly reduced 5-FU induced damage to the oral mucosa via the reduction of oxidative stress and inflammation in pre-clinical rodent models.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, orally taking of probiotics drugs during radiotherapy, chemotherapy and surgery in patients can significantly reduce their side effects by improving the disorder of intestinal microbiota 94 , 95 . Other works also indicated that dietary supplements (prebiotics) 96 or prebiotics 97 could selectively stimulate the growth and activity of internal probiotics to reduce the disorder of intestinal microbiota.…”
Section: Future Directionsmentioning
confidence: 99%